Correct placement of the Essure device detected by transvaginal ultrasound at one month predicts correct placement at three months - Mitchell, Sarah; May, James; Ades, Alex (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Correct placement and tubal occlusion following Essure sterilisation is presently confirmed with imaging 3 months post procedure. Compliance with post procedure imaging is low and non-compliance has been implicated in unintended pregnancies following Essure insertion. Patient adherence to medical advice is known to decrease with time. Earlier imaging may improve compliance. The Aim was to determine if correct placement of the Essure micro-insert detected at 1 month by transvaginal ultrasound (TV US) is predictive of correct placement at 3 months. Methods: Prospective cohort of 31 patients in a single centre who underwent the Essure procedure and had TV US at 1 month and 3 months post procedure. Results: The Essure micro-insert was detected in the accurate position by TV US in all 31 women at both 1 month and 3 months post insertion. Conclusions: Correct placement of the micro-insert detected at 1 month is predictive of correct placement at 3 months. TV US at any time from 1 month could be used as the confirmation test for correct placement of the Essure device. This may provide earlier reassurance to women and improve compliance with follow up potentially reducing numbers of unintended pregnancies. The importance of alternative contraception until 3 months post insertion should still be emphasised.